Peningkatan Keterampilan Diaspora melalui Penulisan Artikel Ilmiah: Skill Enhancement Diaspora through Scientific Article Writing - Yuspin, Wardah; Wardiono, Kelik; Rizka, Rizka; Isman, Isman; Purwandari, Eny (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This service aims to increase employment opportunities for diasporas who take further education abroad, such as in Malaysia, Hong Kong, and Sweden, with manufacturing abroad, such as in Malaysia, Hong Kong, and Sweden, by creating and submitting articles to reputable journals. Submission of articles in reputable journals. The opportunities obtained by students simultaneously bring two challenges, namely the arrival and return stages. In the preparation stage, it is usually related to culture shock because they come to a new place with different weather, different cultures, and different value systems. Also a different value system. Furthermore, when implementing lectures, students are expected to be able to attend lectures and work on assignments to create scientific articles. Assignments to create scientific articles. Moreover, they will experience reverse culture shock at the return stage, such as limited job opportunities in their homeland. Community Service is carried out from September to November when this month is the new school year. In addition, this month, the preparation of students who take master's degrees ends, and they are preparing to return to their homeland. Furthermore, they prepare to return to their homeland. This community service is an effort to help students in the settlement stage deal with culture shock and prepare them for their return home. Shock and prepare students for repatriation. The method used two ways, the first is the delivery of hybrid material, namely through offline and online exposure. The hope is that acquiring journal-writing skills will make it easier for them to follow.